RATING OF ENTERPRISES’ ACTIVITIES BY THE MODIFIED CLUSTER METHOD - Kravets, Tetyana; Kuznetsov, Glib (Ekonomika, 2011)
The problem of improving the methods of enterprise rating estimation is considered in the article. It is proposed to apply an integrated approach to the analysis of the aggregate financial performance of enterprises, based on the modified clustering method which takes into account the possibilities of Kohonen’s self-organizing p>